Thirty-six new species records of moths (Lepidoptera) for Colombia - Blanca Martínez; José Vicente Rodríguez-Mahecha; Rodrigo Bernal (Check List)
Thirty-six species and three genera of moths are recorded for the ﬁrst time in Colombia, in the families Notodontidae (31 spp., 2 genera), Saturniidae (4 spp., 1 genus), and Sphingidae (1 sp.). All records are based on photographs of live individuals attracted to white and UV lights.